2009
DOI: 10.1002/ppap.200800115
|View full text |Cite
|
Sign up to set email alerts
|

Application of Plasma Surface Treatment to Solid‐State Microscopic Particulates

Abstract: The plasma‐assisted improvement of wettability and flowability of fine powders is described. The plasma down‐stream reactor designed for an adequate treatment of particulates allows efficient surface modification and functionalization of particulates. It is discussed that the resulting rapidity of the processes is due to the homogeneous dispersion of particulates in the reactor. This enables intense particle/plasma interaction presumably due to the formation of floating potential sheaths around each single par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Table 5 provides a comparison of the parameter used and the results obtained in this study with those of the studies of Sonnenfeld et al [ 23 ] and Roth et al [ 25 ] where PE‐HD powders were treated in a downstream plasma reactor using Ar/O 2 /HMDSO mixtures as a plasma gas. This comparison is relevant as PE‐HD and PP powders present similar properties (e.g., only carbon and hydrogen in the backbone chain, density, and mean particle size, among others).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 5 provides a comparison of the parameter used and the results obtained in this study with those of the studies of Sonnenfeld et al [ 23 ] and Roth et al [ 25 ] where PE‐HD powders were treated in a downstream plasma reactor using Ar/O 2 /HMDSO mixtures as a plasma gas. This comparison is relevant as PE‐HD and PP powders present similar properties (e.g., only carbon and hydrogen in the backbone chain, density, and mean particle size, among others).…”
Section: Resultsmentioning
confidence: 99%
“…Sonnenfeld et al, [ 22,23 ] Spillmann et al, [ 14,24 ] and Roth et al [ 25 ] presented an alternative process to DPC. This process consists of the simultaneous production and deposition of nanoparticles on the surface of the substrate particles by a homogenous gas phase reaction in a dusty plasma‐enhanced chemical vapor deposition (PECVD) process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sonnenfeld et al showed that due to the formation of floating potential sheath around each particle a homogeneous distribution of particle is established in the reactor which results in the surface treatment time of the order of a tenth of a second instead of hours compared to conventional processes. 11 Roth et al used a two stage plasma processing approach to enhance the flowability and dissolution of salicylic acid powder for pharmaceutical applications. 14 In the first step, the surface of salicylic acid particle was coated with SiO x nanostructures which act as spacers and reduce the prevailing interparticle van der Waals forces, such that the particles can easily flow.…”
Section: Introductionmentioning
confidence: 99%
“…That comprehensive paper describes both laboratory research and industrial applications. Sonnenfeld et al [16] used a capacitively coupled radio-frequency (RF) plasma reactor to improve the wettability and flowability of fine powders made from high-density PE. The formation of floating potential sheaths around each single particle immersed in the plasma enabled intense particle/plasma interaction and thus improved wettability in a treatment time of only 0.12 s. The O/C ratio after this treatment was 0.15.…”
Section: Introductionmentioning
confidence: 99%